Characteristics of Migration from Ukraine to Hungary in the Last Decade - Urbán, Ferenc (Magyar Rendészet, 2023)
The article analyses the changing characteristics of migration from Ukraine to Hungary, also looking at the period before 2010, but mainly at the period between 2010 and 2022. Migration from Ukraine has undergone a number of changes during the period under study due to the socio-economic processes in Ukraine and the war that has broken out in the meantime. Of course, changes in the legal and economic characteristics of Hungary have also had an impact on migration between the two countries. In the course of the analysis, the article takes stock of the changes in legislation and social processes that have taken place and illustrates the impact of these changes on migration with statistical data, highlighting forced migration triggered by the war. The data show that migration from Ukraine has been one of the most important factors influencing the overall migration process in Hungary.